A Inconstitucionalidade da tributação sobre livros, periódicos, jornais e papéis destinados à sua impressão: uma análise acerca das implicações geradas pelo Projeto de Lei nº 3.887/2020 - LAMEIRA, Fernanda Garcia (2022)
The tax immunity of books, newspapers, periodicals, and paper used in its printings is provided by Brazilian legal system since 1946 and was maintained on the current constitutional text to insure certain fundamental rights, such as the freedom of speech, the manifestation of thought, the access to education and the dissemination of culture. From this, as the years went by the tax immunity has been expanded to cover digital books, sticker albums, and etc.; and also, to be projected on PIS/COFINS contributions, in accordance with the law no. 10.865/04. However, on November 7, 2020, the current Economy Minister presented a bill to revoke the zero PIS and COFINS tax rate on books, newspapers, periodicals, and paper used in its printings, raising questions about the constitutionality of the measure. By doing so, the proposed law run counter to the current trend in case law and legislation to extend tax immunity and constitute a downright violation of the above-mentioned fundamental rights, as the increase in payment of taxes or contributions over books, newspapers and periodicals makes it difficult to exercise the freedom of speech or the dissemination of culture, for instance. In addition, the bill no. 3.887/2020 should be regarded as unconstitutional for it violates the principle of seal to social regression because represents a setback in the implementations and concretization of the mentioned rights.